(untitled) (Agricultural Engineering, 2018)
The article analyzes the current state of production of second generation biofuels in the world and evaluates the possibility of launching such production in Ukraine. The work is topical due to the fact that liquid biofuels can replace a certain share of motor fuels consumed in Ukraine, thus contributing to the strengthening of the country’s energy independence. The purpose of the study is to assess feasibility of a project on the production of second generation bioethanol in Ukraine; the task is to carry out a preliminary feasibility study for such a project. The analysis of the study of pure co-substrate fermentation and as a supplement for cattle manure proves that the maximum biogas yield obtained using alcohol stillage in a ratio of 40-80% increased compared to fermentation of pure cattle manure. The use of pure bards compared to the bard and the slurry mixture increases the maximum yield of biogas. It was found that the biogas obtained from the use of alcohol stillage is a high con-sumption of biogas with the methane content of between 70 and 78%.